2019
DOI: 10.1007/s12529-019-09831-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining a Syndemics Network Among Young Latino Men Who Have Sex with Men

Abstract: Background-Although studies consistently find that syndemic indicators are additively associated with increased HIV/STI risk behavior (e.g., condomless anal sex; CAS) among men who have sex with men (MSM), information is lacking about how syndemic indicators are associated with each other. Young Latino MSM are one of the most at-risk groups for acquiring HIV in the U.S. Understanding the associations of syndemic indicators with each other and with CAS may improve understanding of how to enhance sexual and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…But there is a smaller established body of research examining the associations between syndemic indicators and IPV victimization within the sample population. Further, the application of the syndemic framework on Latino SMM has highlighted that depression, CSA, drug use, and problematic drinking represent significant influences on HIV risk within this population (Blashill et al, 2020; Lee et al, 2020; Martinez et al, 2016). More recent research on syndemic factors and health among Latino SMM has incorporated culturally relevant variables (i.e., acculturative stress and immigration) as risk factors of adverse health among this population (González-Guarda et al, 2016; Lee et al, 2020; Martinez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But there is a smaller established body of research examining the associations between syndemic indicators and IPV victimization within the sample population. Further, the application of the syndemic framework on Latino SMM has highlighted that depression, CSA, drug use, and problematic drinking represent significant influences on HIV risk within this population (Blashill et al, 2020; Lee et al, 2020; Martinez et al, 2016). More recent research on syndemic factors and health among Latino SMM has incorporated culturally relevant variables (i.e., acculturative stress and immigration) as risk factors of adverse health among this population (González-Guarda et al, 2016; Lee et al, 2020; Martinez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The association between substance use and IPV in SMM (Buller et al, 2014; Duncan et al, 2018) has been well-established in the larger body of research. Fewer studies have replicated the association in Latino SMM (De Santis et al, 2012, 2014; Lee et al, 2020). Latino SMM report greater rates of substance use and substance-use disorders compared to heterosexual Latino men (Cochran et al, 2007) and non-Latino SMM (Irwin & Morgenstern, 2005; Slater et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural indicators, counted alongside psychosocial factors, were found to be associated with poor ART adherence, detectable viral load, 33,35 and being interrelated, demonstrating a syndemic relationship. 36,37 A study of people living with HIV who inject drugs found lower odds of adherence to HIV medication when participants reported 3 or more psychosocial problems and lower likelihood of being virally suppressed when reporting 4 or more psychosocial problems. 34 For this study, psychosocial problems encompassed both structural (ie, housing instability and incarceration history) and behavioral (ie, experiences of abuse and psychological distress) factors, which were used to develop a count score by adding the number of experienced psychosocial problems and later examined in association with HIV treatment adherence outcomes.…”
Section: Psychosocial and Structural Syndemic Factors Related To Hiv ...mentioning
confidence: 99%